LoopGrafter: a web tool for transplanting dynamical loops for protein engineering. Issue Volume 50:Issue W1(2022) (19th April 2022) - Planas-Iglesias, Joan; Opaleny, Filip; Ulbrich, Pavol; Stourac, Jan; Sanusi, Zainab; Pinto, Gaspar P; Schenkmayerova, Andrea; Byska, Jan; Damborsky, Jiri; Kozlikova, Barbora; Bednar, David
Abstract: The transplantation of loops between structurally related proteins is a compelling method to improve the activity, specificity and stability of enzymes. However, despite the interest of loop regions in protein engineering, the available methods of loop-based rational protein design are scarce. One particular difficulty related to loop engineering is the unique dynamism that enables them to exert allosteric control over the catalytic function of enzymes. Thus, when engaging in a transplantation effort, such dynamics in the context of protein structure need consideration. A second practical challenge is identifying successful excision points for the transplantation or grafting. Here, we present LoopGrafter (https://loschmidt.chemi.muni.cz/loopgrafter/ ), a web server that specifically guides in the loop grafting process between structurally related proteins. The server provides a step-by-step interactive procedure in which the user can successively identify loops in the two input proteins, calculate their geometries, assess their similarities and dynamics, and select a number of loops to be transplanted. All possible different chimeric proteins derived from any existing recombination point are calculated, and 3D models for each of them are constructed and energetically evaluated. The obtained results can be interactively visualized in a user-friendly graphical interface and downloaded for detailed structural analyses. Graphical Abstract: